Madkhol Al-Ittishōl ‘Ala Asāsi Nadzoriyah Ta’līmu Gagne fī Al-Muhādatsah bi Al-Madrasah Al-Qōdirī Al-Mutawassithoh Al-Islāmiyyah Al-Ūlā - Wulandari Wima, Annisa Eriska; Zainuddin El Haj; Asep Maulana (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The purpose of this study is a communicative approach that emphasizes students' communicative abilities, both in formal and informal settings. The characteristics of the communicative approach are presented from the point of view of students, the role of teachers, teaching tools, and educational goals. The communicative approach is viewed in terms of students, the learning process, and goals in education. The main goal of the communicative approach is to make students capable or have communicative competence. The communicative approach is used fully with student centered while the teacher is only as a facilitator. In this study, the communicative approach in learning muhadatsah is applied through Gagne's learning theory in order to increase effectiveness in the development of students who are still difficult to communicate, especially Arabic. In this study, researchers used a descriptive qualitative approach. The data collection methods used were observation, interview, and documentary. Data analysis proposed by Milles & Huberman and researchers used the triangulation method to correct the data. The result of this study is the use of communicative approach in teaching speaking, namely: Communicative approach teaching planning in Al-Qodiri Islamic Junior High School Jember, communicative approach uses strategies and learning theory of Gagne in educational stages to make students play an active role during the educational process, and teachers must also have the skills to teach speaking.